Desenvolvimento de consciência socioambiental em cadeias produtivas de base artesanal: uma proposta metodológica - Alves, Jean Carlos Machado (2010)
This purpose of this project presents a methodology of action for the development of social and environmental awareness in production clusters of craft basis. We studied cluster's basic craft of Dores de Campos e Prados municipalities, both from the middle slopes of Campos das Vertentes in Minas Gerais, which have in the leather craft activity its largest economy. So, based on the experiences of these two cities this study aims at constructing and validating a model for the development of social and environmental awareness in supply chains based on small-scale production clusters, specifically, the activity of leather. We used a literature search, document, contacts with local leaders, applications, interviews, analysis and tabulation of data, carrying out a socio-environmental forum and the creation and validation of methodology for the development of consciousness. As a result it was concluded, among other things, that there are important factors in contemporary and historical growth of productive clusters and also possible solutions using techniques, psychosocial management, recycling and even tax benefits. And the production clusters on based craft is a wide field which lies in the social and environmental awareness theme a vast territory to the development of several studies in the area of knowledge, it doesn`t depend not only on technical, but also on the main factor that is transforming the human being.